C-reactive protein for the diagnosis and prognosis of visceral leishmaniasis caused by Leishmania infantum - Nauside Pessoa da Silva, Maria Nauside; Tárcila Alves de Almeida, Ana; Lamounier Costa, Dorcas; Nery Costa, Carlos Henrique (Revista de Patologia Tropical / Journal of Tropical Pathology, 2022)
Acute-phase reaction (APR) and its marker C-reactive protein (CRP) are heightened in some infectious diseases. APR may contribute to clinical manifestations of systemic inflammation such as hemorrhages, anemia and edema. These symptoms are shared by visceral leishmaniasis (VL), a disease caused by the protozoa Leishmania infantum and L. donovani. The former is zoonotic, hitting mostly children and the immunosuppressed, with higher mortality. As APR and CRP have not been studied in VL caused by L. infantum, we decided to investigate their role as diagnostic and prognostic tools in Brazil. We measured CRP in 136 patients before the treatment of VL and 128 who survived and returned 30 days later and compared it to the clinical presentation, HIV status, and disease severity. Sensitivity for the disease was 97.8% (95%CI: 93.7 - 99.5) and specificity was 85.9% (95%CI: 78.7 - 91.0) with the cut-off of 10mg/L. There was no association of CRP concentration with demographic, clinical and laboratory data. The correlation between pre-and post-treatment levels existed but was poor. Marginal association with the presence of parasites in the bone marrow and death was noticed. The role of APR in the pathogenesis of VL and disease severity remains to be explored. However, the study reveals the significant role of CRP for VL caused by L. infantum and should be routinely required for the diagnosis and follow-up. KEY WORDS: visceral leishmaniasis, kala-azar, acute phase reaction, C-reactive protein, Leishmania infantum, diagnosis, prognosis.